The Flexibility of Islamic Jurisprudence in Zakat al-Fitr: A Comparative Study of the Four Madhhabs on the Payment of Zakat al-Fitr with Money - Muhamad Saefullah (Pascasarjana IAIN Metro, 2026)
The transformation of zakat al-Fitr payment practices from staple food to cash has become an increasingly prominent phenomenon, particularly in Indonesia, and has sparked significant debate regarding its legal validity. This study aims to examine the legal rulings and methods of deriving evidence (istidlāl) concerning zakat al-Fitr from the perspective of the four madhhabs. Employing a normative-comparative approach based on library research, the Qur’an, Hadith, and classical Islamic texts (Kutub al-Turāṡ) are analyzed within the framework of uṣūl al-fiqh. The findings reveal that the Shāfiʿī madhhab along with the Mālikī and Ḥanbalī schools rejects the payment of zakat al-Fitr in cash, as it is considered a taʿabbudī act of worship that must adhere to the form of staple food as prescribed in the Hadith. In contrast, the Ḥanafī madhhab permits it by emphasizing considerations of public benefit (maṣlaḥah) and the equivalence of economic value between food and money. These findings underscore that differences in ijtihād not only reflect methodological diversity but also demonstrate the flexibility of Islamic law in responding to social dynamics contextually.